Delving the influence of socio-economic, demographic and migration factors on utilization of remittances in the agricultural sector in a high out-migrating region in India: Samrat Sarkar, Reshmi R. S. - Samrat Sarkar; Reshmi R. S. (Research in Globalization, 2024)
In developing nations, remittances play a vital role in the development of the society. Remittances serve as a substantial income stream for rural households, empowering them to invest in farming activities, procure resources, and enhance their overall quality of life. This study focuses on investigating remittance utilization patterns in agriculture and how do socio-economic, demographic and migration factors influence remittance utilization patterns in agriculture in the Middle Ganga Plain region (Eastern Uttar Pradesh and Bihar) of India? The study utilizes the data from the Middle Ganga Plain (MGP) migration survey (2021) conducted by the International Institute for Population Sciences, Mumbai. With the help of bivariate analysis, the study explores the relationship between socioeconomic and migration characteristics and the utilization of remittances in the agricultural sector. The Chi-Square test validates the findings, followed by a Binomial Logistic Regression Model for further analysis. The study reveals that marginalized social groups are more inclined to use remittances for agriculture due to their active involvement in agriculture. Furthermore, households with larger landholdings demonstrate an increased likelihood of remittance utilization across all agricultural sectors. Additionally, it was observed that remittances in agriculture were more prevalent among female-headed households. Moreover, parents who are recipients of remittances tend to allocate their funds to agricultural activities. The significant positive correlation between monthly remittance receivers and total agricultural expenses underscores the importance of remittances in rural development. This study provides valuable insights into remittance utilization patterns and associated factors in the agricultural sector, highlighting the need for targeted policies and interventions to enhance the efficient and effective use of remittances in agriculture, ultimately contributing to rural economic growth and development.
Keywords: 330; Out-migration; Remittance; Agriculture; Rural Development; Middle Ganga Plain